Cara nya gimana yah?
a. Lim x=> 0 (-g(x)) = ?
= – Lim x=> 0 g(x) <= <= lim x=> 0 g(x) = √2
= -√2
b. Lim x=> 0 (g(x).f(x)) = ?
= Lim x=> 0 g(x) . Lim x=>0 f(x)
= √2 . 1/2
= 1/2 . √2
c. Lim x=> 0 (f(x)+g(x)) = ?
= Lim x=> 0 f(x) + Lim x=> 0 g(x)
= 1/2 + √2
= 1/2 + 2√2/2
= (1+2√2)/2
d. Lim x=> 0 1/f(x) = ?
= (Lim x=> 0 (1)) / (Lim x=> 0 f(x)) <= Limit konstanta ya cuma konstanta itu sendiri
= 1/(1/2)
= 2
e. Lim x=> 0 (x+f(x)) = ?
= Lim x=> 0 (x) + Lim x=> 0 f(x)
= 0 + 1/2
= 1/2
f. Lim x=> 0 (f(x).cos x/(x-1)) = ?
= (Lim x => 0 f(x) . Lim x=> 0 cos x) / (Lim x=> 0 (x-1))
= (1/2 . cos 0)/(0-1) <= cos 0 = 1
= (1/2.1)/1
= 1/2